2020
DOI: 10.3390/jcm9103301
|View full text |Cite
|
Sign up to set email alerts
|

Wedge-Shaped Implants for Minimally Invasive Treatment of Narrow Ridges: A Multicenter Prospective Cohort Study

Abstract: The present study aims to investigate clinical and patient-centered outcomes after the implant-supported rehabilitation of narrow ridges using a novel wedge-shaped implant. Forty-four patients were treated with the insertion of 59 tissue-level wedge implants (1.8 mm bucco-lingual width) in horizontally atrophic ridges (mean bone width 3.8 ± 0.4 mm). The main outcome measures were: implant stability quotient (ISQ), marginal bone loss (MBL) and patient morbidity. Fifty-eight implants were functioning satisfactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…As suggested by other authors, good compaction of bone trabeculae in bone marrow may justify high ISQ values, especially in the crestal region [30,34,35]. Removal torque is another parameter indicating the relationship between bone and implant surface, especially for in vitro and ex vivo studies [36].…”
Section: Discussionmentioning
confidence: 91%
“…As suggested by other authors, good compaction of bone trabeculae in bone marrow may justify high ISQ values, especially in the crestal region [30,34,35]. Removal torque is another parameter indicating the relationship between bone and implant surface, especially for in vitro and ex vivo studies [36].…”
Section: Discussionmentioning
confidence: 91%
“…However, edentulous ridge width at implant placement site plays a crucial role: an adequate peri-implant bone envelope has a protective effect against the detrimental influence of the aforementioned factors on peri-implant marginal bone stability. In case of insufficient bone width, the clinician may perform horizontal ridge augmentation procedures [ 20 , 21 ], use implants with reduced diameter [ 22 , 23 ] or plan a combination of the above. Nevertheless, there is no agreement in the literature on the minimum amount of bone that should surround an implant.…”
Section: Introductionmentioning
confidence: 99%
“…This technique involves a barrier membrane to exclude soft tissue ingrowth and create a space for the growth of newly mineralized tissue in the affected area. In terms of bone gain, studies have reported that GBR can provide a vertical increase of 2–8 mm, with an implant survival rate ranging from 92.1 to 100% . However, the lack of stability and ability to maintain their shape demonstrated by the biomaterials, which may lead to an unpredictable final alveolar ridge profile, limit the applications of the conventional GBR technique.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of bone gain, studies have reported that GBR can provide a vertical increase of 2−8 mm, with an implant survival rate ranging from 92.1 to 100%. 2 However, the lack of stability and ability to maintain their shape demonstrated by the biomaterials, which may lead to an unpredictable final alveolar ridge profile, limit the applications of the conventional GBR technique. In addition, Li et al reported that the percentage of resorption after 6 months of healing with resorbable membrane coverage reached 37.5%.…”
Section: ■ Introductionmentioning
confidence: 99%